Impact of vitamin D supplementation on modulating heat-shock proteins in postmenopausal women: a randomized, double-blind, placebo-controlled study - Orsatti, Claudio Lera [UNESP]; Orsatti, Fábio Lera; De Souza, João Pedro Esteves Alves; Nahas, Eliana Aguiar Petri [UNESP] (Wolters Kluwer, 2023)
Objective The aim of this study was to examine the effect of vitamin D (VitD) supplementation on serum heat-shock proteins (HSP) in postmenopausal women (PW). Methods In this double-blind, placebo-controlled trial, 160 PW aged 45 to 65 years with amenorrhea 12 months or more were randomized into two groups: 80 PW in VitD group (oral supplementation with 1,000 IU VitD3/d) or 80 PW in placebo group. The PW were assessed at baseline and after 10 months of intervention. Plasma concentrations of 25-hydroxyVitD (25[OH]D) were measured by high-performance liquid chromatography. HSP27/pS78/pS82, HSP27/total, HSP60, HSP70/72, and HSP90α levels were assessed in serum using a multiplexed bead immunoassay. Results HSP27 (pS78/pS82 [P < 0.035] and total [P < 0.001]) levels increased in the supplemented group when compared with the control group. There was no effect of VitD supplementation on HSP60, HSP70/72, and HSP90α levels. Conclusions Vitamin D supplementation increases serum HSP27 level in PW.
Keywords: Heat-shock protein; Postmenopausal women; Randomized clinical trial; Vitamin D